Appropriate integration of workers with physical limitations into a manual workplace "“ development of an assessment tool - Pearson, Jessie T (Rhodes University, Faculty of Science, Department of Human Kinetics and Ergonomics, 2017)
Background: People with physical limitations can contribute significantly to society and the economy, however, barriers to full and effective participation in the labour market often hinder decent employment. In light of this, placement decisions of impaired workers should be based on detailed information of the nature of the jobs available, as well as individual capabilities of the worker. An ergonomics approach to design attempts to achieve an appropriate balance between the capabilities of the worker and the requirements of the task and uses this balance to improve productivity and encourage physical and mental well-being, job satisfaction and safety. A specific analysis tool which can be applied to various workplaces and jobs, and provide information for decisions regarding placement of physically limited workers, will help to increase the percentage of correct placement in an appropriate workplace, resulting in optimum productivity and worker safety. Methods: An assessment tool which allows matching of job requirements and worker capabilities was developed based on a theoretical framework from Mattison and Goebel (2007), as well as principles defined by Almgren and Schaurig (2012) and Demura and Nakada (2010). The tool assesses range of motion, force and time components of the physical requirements of different tasks involved in the job, as well as movement capabilities and limitations of the worker. The tool was pilot tested in a case study with an above the knee amputee working at a research facility. Results: The tool successfully provided information regarding the matching of the work to the identified job. The output of the tool highlighted two tasks which would place the worker at risk due to physical requirements of the tasks being greater than movement capabilities of the worker. These tasks need to be further investigated to determine if accommodations can be made to assist the worker in safely performing the task, or if the job is not suitable for the worker. Conclusions: The tool developed was useful in providing information to inform appropriate placement of the physically limited worker. Further research needs to be done to validate and determine reliability of the tool.
Keywords: Uncatalogued